2019
DOI: 10.12659/msm.917086
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Transperineal Ultrasonography for Diagnosis of Female Occult Stress Urinary Incontinence

Abstract: BackgroundWe evaluated the utility of three-dimensional transperineal ultrasonography in detecting occult stress urinary incontinence in women undergoing anterior pelvic floor reconstruction surgery for severe cystocele.Material/MethodsWe enrolled 207 women with stage III–IV cystocele without urinary stress incontinence. One week before the operation, the patients underwent pelvic floor ultrasonography. We measured the vertical distance between the bladder neck and posterior margin of the pubic symphysis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The bladder neck is located at the junction of the middle and lower third of the pubic symphysis, usually being higher than the pubococcygeal line (the line between the lower edge of the pubic symphysis and the coccyx tip) [ 40 , 41 ]. The angle between the proximal urethral axis and the horizontal tangent line of the bladder base is the posterior vesicourethral angle [ 42 , 43 ], which is normally between 90° and 110°. When the bladder neck is closed at a right angle, the proximal urethra has the strongest closing performance and the greatest resistance.…”
Section: Anatomical Factors Affecting the Urethra ( Figure ...mentioning
confidence: 99%
“…The bladder neck is located at the junction of the middle and lower third of the pubic symphysis, usually being higher than the pubococcygeal line (the line between the lower edge of the pubic symphysis and the coccyx tip) [ 40 , 41 ]. The angle between the proximal urethral axis and the horizontal tangent line of the bladder base is the posterior vesicourethral angle [ 42 , 43 ], which is normally between 90° and 110°. When the bladder neck is closed at a right angle, the proximal urethra has the strongest closing performance and the greatest resistance.…”
Section: Anatomical Factors Affecting the Urethra ( Figure ...mentioning
confidence: 99%
“…Yin et al believed that the longer the funnel shape is, the greater the probability of SUI. 31 Finally, we developed a nomogram model based on the combined model because it can provide more intuitive and accurate results. We evaluated the efficiency of the nomogram, and the results showed that the discrimination of the nomogram was satisfactory, with AUCs of 0.848 and 0.872 in the training and validation cohorts, respectively, which were superior to those of the previous prediction model based on clinical risk factors alone.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in our study emptied both rectum and bladder before the examination, while some other studies had acquired dynamic datasets imaging with a bladder volume of 200-300mL[28], or datasets with no more than 200 mL urine in the bladder [29]. This may result in a lack of pelvic oor morphological data at the leakage point.…”
Section: Discussionmentioning
confidence: 99%